2004
DOI: 10.1038/sj.gt.3302277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GDNF gene transfer into axotomized retinal ganglion cells using in vivo electroporation with a contact lens-type electrode

Abstract: We developed an in vivo electroporation method to introduce foreign genes into retinal ganglion cells (RGCs). After the intravitreous injection of the plasmid gene (20 mg), five electric pulses (6 V/cm, 100 ms duration) were each delivered twice with 5 min interval to the rat eye using a contact lens-type electrode (cathodal) attached to the cornea and a needle electrode (anodal) inserted to the middle of the forehead. The efficiency of the genetic introduction into RGCs and tissue damage to the eyeball was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…This method has been successfully used previously to transfect RGCs. [36][37][38][39] Although ELP does not target RGCs specifically, and transfected cells were distributed not only in the GCL, but also in the inner nuclear layer; most of GCL transfected cells were colocalized with RGCs. We found that cells in the nasal superior or nasal inferior quadrants of the retina were transfected more efficiently than cells in other retinal regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method has been successfully used previously to transfect RGCs. [36][37][38][39] Although ELP does not target RGCs specifically, and transfected cells were distributed not only in the GCL, but also in the inner nuclear layer; most of GCL transfected cells were colocalized with RGCs. We found that cells in the nasal superior or nasal inferior quadrants of the retina were transfected more efficiently than cells in other retinal regions.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 ELP-mediated gene delivery was performed as described previously with minor modifications. 37,39 In brief, animals were anesthetized with an intramuscular injection of 0.8 ml kg À1 of a cocktail containing 5 ml ketamine (100 mg ml À1 ), 2.5 ml xylazine (20 mg ml À1 ), 1.0 ml acepromazine (10 mg ml À1 ), and 1.5 ml normal saline. Four microliters of plasmid DNA (20 mg) was injected into the vitreous cavity with a 34-gauge needle 0.5 mm posterior to the limbus under stereoscopic microscopy.…”
Section: Gene Transfer Into Rgcs With Electroporationmentioning
confidence: 99%
“…73 GDNF gene transfer using an adenoviral vector or electroporation conferred protection of RGCs after optic nerve transaction. 44,74 Collectively, these studies highlight the potential of gene therapy to upregulate retinal neurotrophic factors that stimulate survival and/or regeneration of injured RGCs.…”
Section: Cracking the Case: Gene Therapy Strategies For Rgc Neuroprotmentioning
confidence: 99%
“…This approach has been used successfully to deliver neurotrophic factors and TXN thioredoxin genes to promote RGC survival in several models of optic nerve injury. [33][34][35] Small interference RNA (siRNA) has been successfully delivered to RGCs via injection into the superior colliculus; 36,37 however, the highly invasive nature of this approach limits its clinical application. Alternatively, siRNA can be injected intravitreally, leading to effective delivery to RGCs soon after administration (Figure 2).…”
Section: Tools For Gene Delivery To Injured Rgcsmentioning
confidence: 99%
“…Using electrophoration, GDNF gene transferred into RGCs can increase RGC survival 2-4 weeks after ON transection. 39 Administration of adeno-associated virus (AAV) vector expressing CNTF into the eyes protects RGCs undergoing focal injury and local ischemia in rats. 40 AAV containing basic fibroblast growth factor (bFGF) or BDNF is neuroprotective to RGCs from excitatory injury caused by N-methyl-d-aspartic acid (NMDA) or nerve crush.…”
mentioning
confidence: 99%